Kajian Ekokritik dalam Buku Kumpulan Cerita Rakyat Cilacap - Rizqina, Adina Anisnaeni; Suwandi, Sarwiji; Chaesar, Ari Suryawati Secio (Jurnal Bahasa dan Sastra, 2024)
Environmental issues are a major concern in society. This is caused by human behavior that adversely affects the environment. In relation to these issues, folklore or old literature has great potential to raise human awareness of the importance of maintaining the sustainability of nature. Folktales often contain values of local wisdom, human connection with nature, and moral learning that can be the foundation for ecological awareness. This study aims to describe the representation of ecocriticism in the Cilacap folklore collection book. This research is a qualitative research with content analysis approach. The data source of this research is the book Folklore of Central Java: Cilacap Regency. The sampling technique was done by purposive sampling. The result of this research is ecocriticism in the Cilacap folklore collection book can be known by Greg Garrad's ecocriticism theory (2004) in the form of pollutions, wilderness, disaster (apocalypse), dwelling, animals, and earth. This research contributes greatly to the understanding of ecocriticism and can enrich the repertoire of research on ecocritical studies in folklore which is currently still quite limited in Indonesia.